2016
DOI: 10.1038/ng.3711
|View full text |Cite
|
Sign up to set email alerts
|

Qki deficiency maintains stemness of glioma stem cells in suboptimal environment by downregulating endolysosomal degradation

Abstract: Stem cells including cancer stem cells (CSCs) require niches to maintain stemness, yet it is unclear how CSCs maintain stemness in the suboptimal environment outside their niches during invasion. Postnatal codeletion of Pten and Trp53 in mouse neural stem cells (NSCs) leads to their expansion in the subventricular zone (SVZ) niches but fails to maintain the stemness outside the SVZs. We discovered that QKI is a major regulator of NSC stemness. Qki deletion against Pten−/−Trp53−/− backdrop helps NSCs maintain t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
104
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(113 citation statements)
references
References 48 publications
(61 reference statements)
8
104
0
Order By: Relevance
“…Thus, QKI may play a dual role in cancer progression, limiting the initial formation of tumours but increasing their subsequent invasiveness through regulating the splicing of different target genes, such as through promotion of mesenchymal ENAH splicing. It is also important to note that although QKI-5 knockdown produced modest and inconsistent effects on gene expression ( Fig EV4), we cannot rule out that QKI-5 may also directly or indirectly influence specific mRNA or miRNAs to regulate different aspects of cancer progression, as has been reported in other contexts (Chen et al, 2012;Lu et al, 2014;Yu et al, 2014;Shingu et al, 2017;Zhou et al, 2017). Similarly, QKI-5 also regulates circRNA formation during HMLE cell EMT (Conn et al, 2015), and although the functions of these molecules remain poorly understood, they could contribute to epithelialmesenchymal plasticity.…”
Section: Discussionmentioning
confidence: 81%
“…Thus, QKI may play a dual role in cancer progression, limiting the initial formation of tumours but increasing their subsequent invasiveness through regulating the splicing of different target genes, such as through promotion of mesenchymal ENAH splicing. It is also important to note that although QKI-5 knockdown produced modest and inconsistent effects on gene expression ( Fig EV4), we cannot rule out that QKI-5 may also directly or indirectly influence specific mRNA or miRNAs to regulate different aspects of cancer progression, as has been reported in other contexts (Chen et al, 2012;Lu et al, 2014;Yu et al, 2014;Shingu et al, 2017;Zhou et al, 2017). Similarly, QKI-5 also regulates circRNA formation during HMLE cell EMT (Conn et al, 2015), and although the functions of these molecules remain poorly understood, they could contribute to epithelialmesenchymal plasticity.…”
Section: Discussionmentioning
confidence: 81%
“…In contrast, QKI‐6 knockdown inversely affected the bladder cancer 5637 cells. Although QKI‐6 data in human cancer are limited, our current data further support a role for QKI‐6 in different human cancers . Our current study in bladder cancer using both ex vivo and in vitro approaches is novel, as our data indicate that QKI‐6 plays a tumour suppressive role in bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, altered QKI expression was implicated in various human cancers, including colorectal cancer, 33 paediatric brain tumours, 34 glioma, 35 renal clear cell carcinoma, 9 lung cancer 17 and prostate cancer. 18 In this study, we measured QKI-6 expression and determined its role in regulating bladder cancer in vitro and in vivo, and we also investigated the molecular mechanism underlying QKI-6's effect in bladder cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…GSCs essentially received positive signals from endothelial cells and pericytes, such as ligand/receptor triggers of stemness pathways and adhesion components of the extracellular matrix 13,14,15,16,17 . They are also protected in rather unfavorable conditions where their stemness traits resist hypoxic stress, acidification, and nutrient deprivation 11,12,18 . Recently, it has been suggested that this latter capacity is linked to the function of the RNA binding protein QKI in the down-regulation of endocytosis, receptor trafficking and endo-lysosome-mediated degradation 18 .…”
Section: Introductionmentioning
confidence: 99%